Stronger Digital Leadership for Greater Business Strategy: A Study Using Mixed Methods - Yeny Yusuf; Martani Huseini; Effy Zalfiana Rusfian (Journal of Economics and Behavioral Studies, 2023)
This study analyzes the influence of Digital Leadership (DL) on Digital Business Strategy (DBS) in an organization as an activity with a digital systems mindset even though it does not only use digital technology when implementing it. The research model was tested on a multinational company in the field of computer technology and information systems in Indonesia, headquartered in Japan, and has a long history of advocating personal and environmental harmony. A survey given to respondents in the category of senior positions representing the company is one of the strengths of this research. To carry out the analysis, the survey was processed using mixed methods that combine qualitative and quantitative approaches. The results show DL has a significant influence on DBS and this DL and DBS evaluation model can be used by organizations that want to assess their DL and DBS, as a basic reference to review governance, policies, and business strategies that support competitiveness and business sustainability. Further research can explore indicators of digital leadership and digital business strategy in this study according to the locus and character of the unit of analysis and the role of government regulation as one of the external parties supporting the company's business.